1998
DOI: 10.1046/j.1365-2265.1998.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of long‐term GH replacement therapy on quality of life in adults with GH deficiency

Abstract: These results indicate that the previously reported beneficial effects of GH therapy on quality of life in GH-deficient adults are sustained during long-term therapy. In addition, they suggest that, once started, GH therapy should be continued for at least 6 months before judgements are made regarding its efficacy in improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 19 publications
9
65
1
Order By: Relevance
“…Specifically, because it relates to the findings of GHD and hypogonadism in this study, GH replacement is known to improve QoL in patients with adult-onset GHD and helps reduce fat mass and improve exercise capacity. 51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, because it relates to the findings of GHD and hypogonadism in this study, GH replacement is known to improve QoL in patients with adult-onset GHD and helps reduce fat mass and improve exercise capacity. 51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistently observed complaints in untreated adult patients with GH deficiency (GHD) are related to energy levels, vitality, mental fatigue, emotional reactions, social isolation and anxiety (4)(5)(6)(7)(8). Additionally, reduced self-confidence, disturbed sex life (6), decreased physical mobility (4), dissatisfaction with body image (9), poor memory (10), reduced cognitive function and decreased mood (11), as well as attention deficits (12) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, their use has led to a large variation in results and their interpretation with respect to the effects of GHD and GH replacement therapy on QOL (8,9). However, large-scale studies have since demonstrated that patients with GHD have a lower level of perceived QOL compared with a normative population (10), and that QOL in adults with GHD can be improved during and after GH replacement therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%